THE DEVELOPMENT OF PRACTICUM MODULE COMPUTER SKILL AND INFORMATION MANAGEMENT BY INQUIRY APPROACH FOR STUDENTS CLASS X MULTIMEDIA SMK TI BALI GLOBAL SINGARAJA - Luh Putu Wijayanti (Universitas Pendidikan Ganesha, 2012)
This research aim (1) To design development and implement the practicum modules skills computer and information management by inquiry approach. Class X Multimedia SMK TI Bali Global Singaraja. (2) To find out the responds of the students Class X Multimedia SMK TI Bali Global Singaraja towards development of the practicum modules KKPI by inquiry approach.The kind of research that used in this research is (Research and Development or R&D) by the model development Dick and Carrey. This research involved the students class X Multimedia SMK TI Bali Global Singaraja year 2011/2012. The source of the students data gathered by using an interview method. The validation of the media study based on inquiry approach and also the students’ responds gathered by using questioner method. That gathered data analyzed descriptively.The development of practicum module computer skill and management by inquiry approach used some steps draft development. The result,of the analyzed data of the students’ responds showed that the percentage of the students who gave very positive responds 70%, the percentage of the students who gave positive responds 30% and there we negative or even very negative. The average score gathered from the students were 61. That score showed that the students respond the practicum module approach are on a very positive category.Keyword: Practicum Module, Inquiry, Computer Skill and Information Management.